A randomised assessment of image guided radiotherapy within a phase 3 trial of conventional or hypofractionated high dose intensity modulated radiotherapy for prostate cancer. (January 2020) - Murray, Julia; Griffin, Clare; Gulliford, Sarah; Syndikus, Isabel; Staffurth, John; Panades, Miguel; Scrase, Christopher; Parker, Chris; Khoo, Vincent; Dean, Jamie; Mayles, Helen; Mayles, Philip; et al.
Highlights: Introduction of daily online prostate IGRT was feasible in a national randomised trial. Dosimetric benefits seen in patients treated with IGRT and reduced CTV-PTV margins. Overall side effect profiles were acceptable in all groups but lowest with IGRT and reduced margins. Abstract: Background and purpose: Image-guided radiotherapy (IGRT) improves treatment set-up accuracy and provides the opportunity to reduce target volume margins. We introduced IGRT methods using standard (IGRT-S) or reduced (IGRT-R) margins in a randomised phase 2 substudy within CHHiP trial. We present a pre-planned analysis of the impact of IGRT on dosimetry and acute/late pelvic side effects using gastrointestinal and genitourinary clinician and patient-reported outcomes (PRO) and evaluate efficacy. Materials and methods: CHHiP is a randomised phase 3, non-inferiority trial for men with localised prostate cancer. 3216 patients were randomly assigned to conventional (74 Gy in 2 Gy/fraction (f) daily) or moderate hypofractionation (60 or 57 Gy in 3 Gy/f daily) between October 2002 and June 2011. The IGRT substudy included a second randomisation assigning to no-IGRT, IGRT-S (standard CTV-PTV margins), or IGRT-R (reduced CTV-PTV margins). Primary substudy endpoint was late RTOG bowel and urinary toxicity at 2 years post-radiotherapy. Results: Between June 2010 to July 2011, 293 men were recruited from 16 centres. Median follow-up is 56.9(IQR 54.3–60.9) months. Rectal and bladder dose-volume and surface percentages were significantly lower in IGRT-R compared to IGRT-S group; (p < 0.0001). Cumulative proportion with RTOG grade ≥ 2 toxicity reported to 2 years for bowel was 8.3(95% CI 3.2–20.7)%, 8.3(4.7–14.6)% and 5.8(2.6–12.4)% and for urinary 8.4(3.2–20.8)%, 4.6(2.1–9.9)% and 3.9(1.5–9.9)% in no IGRT, IGRT-S and IGRT-R groups respectively. In an exploratory analysis, treatment efficacy appeared similar in all three groups. Conclusion: Introduction of IGRT was feasible in a national randomised trial and IGRT-R produced dosimetric benefits. Overall side effect profiles were acceptable in all groups but lowest with IGRT and reduced margins. ISRCTN: 97182923.